The importance of the physical modelling to solve coastal engineering complex problems -Experience from some PhD Research Projects. - Francisco Taveira Pinto (2010)
Models represent the real problem with some simplifications. Despite the shortcomings inherent in experimentalphysical modelling, scale models are the best tool that an engineer has to discover and verify engineering solutions andto improve upon and verify numerical approaches. In this paper three examples of coastal engineering problems,related with PhD research projects are presented. With these examples it is intended to present the main issues and thedifficulties had during its execution.